Genome-wide DNA methylation analysis in melanoma reveals the importance of CpG methylation in MITF regulation - Lauss, Martin (J Invest Dermatol, 2015)
The microphthalmia-associated transcription factor (MITF) is a key regulator of melanocyte development and a lineage-specific oncogene in melanoma; a highly lethal cancer known for its unpredictable clinical course. MITF is regulated by multiple intracellular signaling pathways although the exact mechanisms that determine MITF expression and activity remain incompletely understood. In this study, we obtained genome-wide DNA methylation profiles from 50 stage IV melanomas, normal melanocytes, keratinocytes and dermal fibroblasts, and utilized The Cancer Genome Atlas (TCGA) data for experimental validation. By integrating DNA methylation and gene expression data we found that hypermethylation of MITF and its co-regulated differentiation pathway genes, corresponded to decreased gene expression levels. In cell lines with a hypermethylated MITF-pathway, over-expression of MITF did not alter the expression level or methylation status of the MITF pathway genes. In contrast however, demethylation treatment of these cell lines induced MITF-pathway activity, confirming that gene-regulation was controlled via methylation. The discovery that the activity of the master regulator of pigmentation, MITF, and its downstream targets may be regulated by hypermethylation has significant implications for understanding the development and evolvement of melanoma.